2020
DOI: 10.12968/bjon.2020.29.13.788
|View full text |Cite
|
Sign up to set email alerts
|

Student experiences of nursing on the front line during the COVID-19 pandemic

Abstract: This article provides the reflections of three University of Salford student nurses, one of whom has now qualified as a registered nurse, who have experience of working on the frontline during the COVID-19 pandemic. The crucial role that the students personal tutor is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 2 publications
2
28
0
1
Order By: Relevance
“…The behavior of extreme caution was noted in the behaviors that went beyond recommendations in isolation and cleaning. The findings indicating fear, anxiety, stress, and uncertainty are similar to those of recent research in Croatia (Lovrić et al, 2020), the United Kingdom (Leigh et al, 2020), and China (Huang et al, 2020;Zhi et al, 2020). In this study, compared with the original model, there was not a lack of regard for those affected, but a strong feeling of concern, mostly related to their own family with fewer indications of a more global concern.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The behavior of extreme caution was noted in the behaviors that went beyond recommendations in isolation and cleaning. The findings indicating fear, anxiety, stress, and uncertainty are similar to those of recent research in Croatia (Lovrić et al, 2020), the United Kingdom (Leigh et al, 2020), and China (Huang et al, 2020;Zhi et al, 2020). In this study, compared with the original model, there was not a lack of regard for those affected, but a strong feeling of concern, mostly related to their own family with fewer indications of a more global concern.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study in China by Huang et al (2020) found both nurses and nursing students lacked the necessary coping strategies when encountering the stressors of the COVID-19 crisis. Leigh et al (2020) found nursing students in the United Kingdom working in the clinical setting during the COVID-19 pandemic described varied experiences with difficult decisions. In a study of medical, nursing, and pharmacy students about concerns while working with infectious diseases, Patel et al (2017) found students were more fearful and less willing to work during outbreaks with respira-…”
mentioning
confidence: 99%
“…A survey of US medical students, also at the start of the pandemic, echoed concerns about interrupted training, but their concerns were balanced by their desire to serve the sick (Gallagher & Schleyer, 2020). Sentiments from medical and nursing students worldwide reflect a positive regard for their career choice (Leigh et al, 2020; Leong, & Sarohia, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Compounded by a lack of preparedness for a pandemic, healthcare facilities faced significant surges of critical care patients complicated by an inadequate infrastructure including too few ICU beds, ventilators, personal protective equipment (PPE), and in some cases, capacity for the rising numbers of the deceased. [1] Issues encountered by our nursing students included employment staffing shortages, reassignments to unfamiliar units, mandatory overtime, fear and anxiety over exposure, becoming infected by COVID-19, and the risk of transmitting the virus to family members (see Table 1). Anxiety increased from economic uncertainty [16] due to temporary or permanent furloughs of nurses in units that were not COVID-focused.…”
Section: Professional Stressorsmentioning
confidence: 99%
“…[1][2][3] In addition to their clinical positions, many working nurses are students in degree programs with added responsibilities and burdens, including time management issues and the ability to focus on schoolwork during the heightened clinical demands of the pandemic. [4,5] While numerous reports have described the difficult conditions for nurses working in COVID-19 clinical environments, [6][7][8] and the need for adaptations in nursing curricular content to prepare students for present and future pandemics, [1,9,10] few accounts have detailed the logistic, academic, and emotional experiences for students and faculty in nursing education during this unprecedented time. This article is a descriptive summary, supported by unsolicited anecdotal reports from student emails to faculty, detailing how students persevered and balanced their roles as professional nurses in clinical environments and as nursing students during the period of March-July, 2020.…”
Section: Introductionmentioning
confidence: 99%